Utilizing MSK Ultrasound for Comprehensive Assessment of the Femoral Trochlea: A Game Changer in Sports Medicine - Robert C Manske; Mike Voight; Phil Page; Chris Wolfe (International Journal of Sports Physical Therapy)
Musculoskeletal (MSK) ultrasound has emerged as a valuable tool for sports physical therapists in the assessment and treatment of various knee pathologies. Its ability to provide high-resolution images of soft tissue and superficial bone surfaces makes it especially useful for sports physical therapists and orthopedic clinicians. Specifically, MSK-ultrasound is increasingly recognized as a potent tool for the assessment of the femoral trochlea. Its non-invasive nature and dynamic imaging capabilities make it particularly suited for visualizing the femoral trochlea, a critical component in knee function and biomechanics. The use of MSK ultrasound in the evaluating the femoral trochlea provides sports medicine professionals with a dynamic, non-invasive, and cost-effective means to diagnose, and monitor knee-related injuries. This article delves into the utility of MSK ultrasound in the anatomical and functional assessment of the femoral trochlea, elucidating its benefits, limitations, and clinical implications for athletes.